Análise e proposta de melhoria no processo de planejamento de materiais: um estudo de caso em uma concessionária de energia elétrica da Região Sul do País - Camargo, Manoel Sebastião (Universidade do Vale do Rio dos Sinos, 2016)
This project has the purpose of depicting all reasons that explain goods supply problems in an energy distribution company of South Brazil, proposing processes improvements. Key valuable processes regarding materials planning were selected for detailed mapping, using BPM (Business Process Management) techniques for revealing valuable opportunities with processes flows, handoffs interactions, actual state diagnosis and future state developments. This work had developed extensive literature review aiming to present materials planning best practices and solutions useful for a distribution energy company. The Brazilian energy sector demands supply solutions with high flexibility capabilities, providing competitive advantage and adaptability for new management challenges.
Keywords: Business process management; BPM; Distribuidora de energia elétrica; Planejamento de materiais; Energy distribution companies; Materials planning